Identification of differentially methylated regions using streptavidin bisulfite ligand methylation enrichment (SuBLiME), a new method to enrich for methylated DNA prior to deep bisulfite genomic sequencing - Ross, Jason P. (Landes Bioscience, 2013)
We have developed a method that enriches for methylated cytosines by capturing the fraction of bisulfite-treated DNA with unconverted cytosines. The method, called streptavidin bisulfite ligand methylation enrichment (SuBLiME), involves the specific labeling (using a biotin-labeled nucleotide ligand) of methylated cytosines in bisulfite-converted DNA. This step is then followed by affinity capture, using streptavidin-coupled magnetic beads. SuBLiME is highly adaptable and can be combined with deep sequencing library generation and/or genomic complexity-reduction. In this pilot study, we enriched methylated DNA from Csp6I-cut complexity-reduced genomes of colorectal cancer cell lines (HCT-116, HT-29 and SW-480) and normal blood leukocytes with the aim of discovering colorectal cancer biomarkers. Enriched libraries were sequenced with SOLiD-3 technology. In pairwise comparisons, we scored a total of 1,769 gene loci and 33 miRNA loci as differentially methylated between the cell lines and leukocytes. Of these, 516 loci were differently methylated in at least two promoter-proximal CpG sites over two discrete Csp6I fragments. Identified methylated gene loci were associated with anatomical development, differentiation and cell signaling. The data correlated with good agreement to a number of published colorectal cancer DNA methylation biomarkers and genomic data sets. SuBLiME is effective in the enrichment of methylated nucleic acid and in the detection of known and novel biomarkers.